Pelaksanaan Manajemen Berbasis Madrasah Dalam Meningkatkan Mutu Pendidikan Di Ma Putra As’adiyah Pusat Sengkang - Hamka Anas; A. Marjuni; Baharuddin Baharuddin (LPPM IAIN Sorong, 2024)
Madrasahs must upgrade their managerial practices in an effort to better address the demands and difficulties of society and bring about better transformation. Madrasahs must enhance their management practices in order to better address the demands and issues of the community and bring about better transformation. The purpose of this essay is to explain how MA Putra As'adiyah Pusat Sengkang has improved the quality of education by implementing madrasah-based administration. Descriptive qualitative research is what this study is. Techniques for gathering data included recordkeeping, interviewing, and observation. The procedures of reduction, presentation, and verification were used to process the data. Finally, a second verification of the data was performed using triangulation. The findings indicated that: 1) Using MBM to raise the standard of instruction at Massachusetts Putra As'adiyah Pusat Sengkang is managed using four different components. The learning process planning (prota, promes, KKM, syllabus, and lesson plans) and learning methodology are included in the planning component. The contemporary, expert, and collaborative way that MBM is implemented is the organizational component. The MBM implementation component uses the formalism and organism paradigm to highlight the learning component. The administrative, academic, and clinical components comprise the supervisory aspect. 2) MBM is working to raise the standard of education at MA As'adiyah Pusat Sengkang by enhancing the administration, curriculum management, student body composition, faculty quality, and infrastructure and facility quality.